2013
DOI: 10.1002/jrs.4349
|View full text |Cite
|
Sign up to set email alerts
|

Validation of isotope dilution surface‐enhanced Raman scattering (IDSERS) as a higher order reference method for clinical measurands employing international comparison schemes

Abstract: Isotope dilution surface‐enhanced Raman scattering (IDSERS) was established as a higher order reference measurement method for clinical measurands in international comparison schemes and in direct comparison with established mass spectrometric methods. IDSERS represents the most accurate and precise quantitative Raman technique and is capable of providing SI‐traceable amount‐of‐substance measurements. IDSERS has now been validated by participation in two international ring trials organized within the framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The use of isotopologues for SERS was first reported by van Duynes' group for systematic studies of single molecule detection of crystal violet [97]. For quantitative analysis, this approach is often termed isotope dilution surfaceenhanced Raman scattering (IDSERS) [98], and has been used to improve quantification between different batches of nanoparticles [99] and to effect the absolute quantification of markers in serum [100] as well as human plasma [101], and for the analysis of nicotine content in electronic cigarettes [102].…”
Section: The Use Of Internal Standards and Isotopologuesmentioning
confidence: 99%
“…The use of isotopologues for SERS was first reported by van Duynes' group for systematic studies of single molecule detection of crystal violet [97]. For quantitative analysis, this approach is often termed isotope dilution surfaceenhanced Raman scattering (IDSERS) [98], and has been used to improve quantification between different batches of nanoparticles [99] and to effect the absolute quantification of markers in serum [100] as well as human plasma [101], and for the analysis of nicotine content in electronic cigarettes [102].…”
Section: The Use Of Internal Standards and Isotopologuesmentioning
confidence: 99%
“…The IL approach has also been carried out by Zakel and Stosch to develop a quantitative method for measuring creatinine as a biomarker in human serum. 10 This study concluded that the combination of SERS and IL had proved to be a valuable approach for clinical diagnostic measurements.…”
Section: Introductionmentioning
confidence: 84%
“…The simplified preparation concept for a controlled formation for a SERS‐active immunosensor greatly improves the applicability of this approach and allows a larger scale implementation. Furthermore, a quantification principle will be established utilizing the isotope dilution (ID) technique, which is mostly used in mass spectrometry, but which has also been shown to work excellently when combined with Raman spectroscopy . Besides the advantages of having molecular specificity, accuracy and a high sensitivity during quantification, an ID‐SERS approach also could provide SI‐traceability of the measurement results when combined with well‐characterized reference materials.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, so‐called reference measurement methods must be provided, which are ideally connected directly to the international system of units (SI) . It has already been demonstrated that SERS‐based methods are basically suitable for realizing the required SI‐traceability . However, the establishment of a reference measurement method to quantify extremely low concentrations of large biomarker molecules such as tau protein is still challenging and time consuming.…”
Section: Introductionmentioning
confidence: 99%